2017
DOI: 10.1016/j.ijid.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo hemorrhagic fever in pregnancy: A systematic review and case series from Russia, Kazakhstan and Turkey

Abstract: HighlightsCCHF in pregnancy is rare but has high rates of maternal (34%) and fetal mortality (59%).Maternal hemorrhage is associated with maternal and fetal/neonatal death.Nosocomial transmission of CCHF from 6/37 index pregnant cases resulted in 38 cases.Early recognition and risk-assessment allows appropriate IP & C precautions and supportive care provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
(33 reference statements)
2
25
1
Order By: Relevance
“…Here, we were only able to examine female reproductive tissues, so whether these findings extend to male reproductive tissues and any implications for sexual transmission remain to be determined. Several reports focused on CCHF in pregnant women and outcomes in neonates [34][35][36][37][38][39], but to date, there is only one report of potential sexual transmission [40]. Our data support future investigations into reproductive infection, pathology, and implications for CCHFV transmission, as well as using both female and male models of disease for these and other pathogenesis studies.…”
Section: Differential Cytokine Expression In Mice Infected With Eithesupporting
confidence: 74%
“…Here, we were only able to examine female reproductive tissues, so whether these findings extend to male reproductive tissues and any implications for sexual transmission remain to be determined. Several reports focused on CCHF in pregnant women and outcomes in neonates [34][35][36][37][38][39], but to date, there is only one report of potential sexual transmission [40]. Our data support future investigations into reproductive infection, pathology, and implications for CCHFV transmission, as well as using both female and male models of disease for these and other pathogenesis studies.…”
Section: Differential Cytokine Expression In Mice Infected With Eithesupporting
confidence: 74%
“…In another report, two pregnant patients in Turkey survived and gave birth to healthy babies by vaginal delivery [76] . A review of pregnant patients reported that maternal mortality was 34% (14/41) and fetal/neonatal mortality was 58.5% (24/41), and the presence of hemorrhage was associated with maternal and fetal mortality [77] .…”
Section: Prognostic Factors Fatality and Discharge Criteriamentioning
confidence: 99%
“…The disease was first reported in 1944. However, CCHF transmission has been reported globally since 1998 [6]. Today, the infection is endemic, with sporadic outbreaks and a 10-40% case fatality rate [7].…”
Section: Introductionmentioning
confidence: 99%